Dopamine D1 receptors facilitate GABAA synaptic currents in the rat substantia nigra pars reticulata - Radnikow, Gabriele; Misgeld, Ulrich (The journal of neuroscience, 1998)
GABA neurons in the substantia nigra pars reticulata receive input from GABAergic fibers originating in the forebrain. The role of dopaminergic D1 receptors located on these fibers was investigated using tight-seal whole-cell recordings from visually identified pars reticulata neurons of rat substantia nigra slices. Nondopaminergic pars reticulata neurons were characterized by their electrophysiological properties. Postsynaptic currents evoked by minimal stimulation in the presence of ionotropic glutamate receptor antagonists were blocked by bicuculline, indicating that they were GABAA IPSCs. Evoked GABAA IPSCs were potentiated by D1 receptor agonists. After application of D1 receptor agonists, miniature IPSCs [recorded in the presence of tetrodotoxin (TTX) and the Ca2+ channel blocker Cd2+] increased in frequency but not in amplitude. Effects of D1 receptor stimulation were mimicked by forskolin, as expected, if a cAMP-dependent mechanism was involved. The D1 antagonist SCH23390 blocked the effects of the agonists, and perfusion with SCH23390 resulted in a reduction of evoked IPSCs. In TTX and Cd2+, which prevented dopamine release, the D1 antagonist had no effect on miniature IPSCs. Blocking of monoamine uptake by imipramine increased the amplitude of evoked IPSCs. We conclude that dopamine released from dendrites of dopaminergic neurons enhances GABA release in the pars reticulata of the substantia nigra through D1 receptors presumably located on striatonigral afferents. These D1receptors, thereby, can reinforce D1 receptor-mediated activation of striatal projection neurons that inhibit the inhibitory output neurons of the basal ganglia in substantia nigra.